Chitosan enhances the antimicrobial photodynamic inactivation mediated by Photoditazine® against Streptococcus mutans - de Souza, Cheyenne Marçal [UNESP]; Garcia, Maíra Terra [UNESP]; de Barros, Patrícia Pimentel [UNESP]; Pedroso, Lara Luise Castro [UNESP]; Ward, Rafael Araújo da Costa [UNESP]; Strixino, Juliana Ferreira; Melo, Vânia Maria Maciel; Junqueira, Juliana Campos [UNESP] (Elsevier, 2020)
Chitosan (CS), a biopolymer with intrinsic antimicrobial activity, can increase antimicrobial photodynamic inactivation (aPDI). The aim of this study was to evaluate the capacity of CS to potentiate the efficacy of Photoditazine® (PDZ)-mediated aPDI of the cariogenic bacterium Streptococcus mutans. CS effectively augmented the effects of aPDI, with reductions of approximately 4.5 logs in both planktonic and biofilm states. The combined treatment was also capable of reducing the number of S. mutans cells and amount of extracellular matrix in biofilms formed on enamel surfaces, which were characterized using scanning electron microscopy analysis. Furthermore, CS increased the absorption of PDZ by S. mutans cells. The combination of CS with PDZ-mediated aPDI is hence a promising antimicrobial approach against S. mutans and may be useful to control dental caries.
Keywords: Antimicrobial photodynamic inactivation; Chitosan; Photoditazine®; Streptococcus mutans